Perception of Islamic student interest in stock investment: financial literacy, financial behavior, and risk perception - Kumba Digdowiseiso (LPMP Imperium, 2022)
Research that focuses on the perception of Islamic students in investing has not been carried out. Therefore, this study aims to analyze the factors (financial literacy, financial behavior, and risk perception) that arouse interest in investing in Muslim students. This research is sourced from primary data obtained from respondents through the distribution of questionnaires. The data collected can be processed 100 from a sample of 195 respondents, which is measured by the Slovin formula. The sample was taken by means of convenience sampling, which is part of the population targeted in this study, namely students who are Muslim who are students of the National University of the Faculty of Economics and Business. Descriptive analysis and multiple linear regression analysis are data analysis techniques used in this study with the program STATA Statistics version 16. Based on study’s results, it was found that financial literacy and financial behavior variables had a significant and positive effect on investment interest, while risk perception was not significant in attracting investment interest in Muslim students in the management study program of the Faculty of Economics and Business, National University. Suggestions in the future that it is necessary to promote financial literacy and provide training with insight into financial literacy and financial behavior in promoting investment interest, especially in Muslim students.